2007
DOI: 10.2355/isijinternational.47.1
|View full text |Cite
|
Sign up to set email alerts
|

Computer Simulation of Microstructure Evolution in Low Carbon Sheet Steels

Abstract: Models of microstructure evolution in steels are reviewed. The emphasis of the review is on low carbon sheet steels both hot-rolled and cold-rolled and annealed. First the state-of-the-art on industrial microstructure process models is presented. The individual model concepts for grain growth, recrystallization, precipitation and phase transformations are briefly discussed. The development from empirically-based models to physically-based models is identified as a key issue to have increased predictive capabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(43 citation statements)
references
References 129 publications
0
38
0
Order By: Relevance
“…Tests of thin foils performed using a transmission electron microscope revealed that the hardening of steel S700MC was primarily affected by dispersive (Ti,Nb)(C,N)-type precipitates sized from several nanometres to between ten and twenty nanometres. The precipitation hardening was mainly triggered by dispersive precipitates of several nanometres in size, precipitated in the steel (in ferrite) during cooling ( Figure 2) [28][29][30][31][32]. Particles sized above twenty nanometres did not significantly contribute to precipitation hardening, yet they restrained the recrystallised austenite grain growth, favouring the formation of the fine-grained structure [28,[33][34][35][36][37].…”
Section: Resultsmentioning
confidence: 99%
“…Tests of thin foils performed using a transmission electron microscope revealed that the hardening of steel S700MC was primarily affected by dispersive (Ti,Nb)(C,N)-type precipitates sized from several nanometres to between ten and twenty nanometres. The precipitation hardening was mainly triggered by dispersive precipitates of several nanometres in size, precipitated in the steel (in ferrite) during cooling ( Figure 2) [28][29][30][31][32]. Particles sized above twenty nanometres did not significantly contribute to precipitation hardening, yet they restrained the recrystallised austenite grain growth, favouring the formation of the fine-grained structure [28,[33][34][35][36][37].…”
Section: Resultsmentioning
confidence: 99%
“…Models for this transformation had first been developed for plain carbon steels and subsequently applied to microalloyed steels. 32,48,49) These models remain applicable to AHSS with higher alloying contents. 33,35,38) Following the previously established approach the austenite-to-ferrite transformation kinetics is described with a model consisting of three submodels, i.e.…”
Section: Austenite-to-ferrite Transformation Modelmentioning
confidence: 99%
“…In particular, the description of the bainite reaction for run-out table cooling requires further work. 49) Figure 5 shows the results for the critical cooling rates of bainite and martensite formation in the present steels. These cooling rates tend to decrease with increasing ferrite fraction since the associated increase of carbon concentration in the remaining austenite leads to higher stability of the austenite phase.…”
Section: Figmentioning
confidence: 99%
“…2 To take advantage of the potential of these phase transformations it is critical to optimize processing paths for producing materials with the desired properties. Although significant progress has been made in developing knowledge-based process models for the steel industry, [3][4][5][6] these models still require numerous empirical parameters that are typically determined from time-consuming laboratory experiments. Thus, these models are, strictly speaking, limited to the investigated steel chemistries and processing conditions.…”
Section: Introductionmentioning
confidence: 99%